Pengaruh Ekoliterasi dan Literasi Spasial Terhadap Kemampuan Pemecahan Masalah Lingkungan Siswa - Novi Aulia Sari; Bambang Syaeful Hadi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to analyze the levels of ecoliteracy, spatial literacy, and environmental problem-solving ability among high school students in Medan City, as well as to examine the influence of ecoliteracy and spatial literacy on students’ environmental problem-solving abilities. This research employed a correlational design using a survey approach. The participants consisted of 343 high school students in Medan City, selected through proportional random sampling. The research instruments included tests and questionnaires. The ecoliteracy test instrument for the environmental knowledge dimension and the spatial literacy test were scored dichotomously, while the ecoliteracy questionnaire measuring environmental care attitudes and environmental problem-solving ability was assessed using a Likert scale. Data were analyzed using SEM-PLS analysis with SmartPLS 3 software. The results showed that: (1) ecoliteracy had a significant effect on students’ environmental problem-solving ability, as indicated by a t-statistic value of 11.378 and a p-value of 0.000; (2) spatial literacy also had a significant effect on environmental problem-solving ability, with a t-statistic value of 9.093 and a p-value of 0.000; and (3) ecoliteracy and spatial literacy jointly contributed 56.4% to students’ environmental problem-solving ability, which is categorized as moderate. This study provides empirical evidence that ecoliteracy and spatial literacy are two complementary constructs in shaping students' environmental problem-solving abilities. Through the integration of these competencies and the use of geospatial technology, students can develop evidence-based and contextual solutions, enabling them to become a generation that is responsive to real-world environmental challenges such as climate change and other complex environmental issues.